Organization and decision - Luhmann, Niklas 1927-1998; Baecker, Dirk 1955- (Cambridge University Press, 2018)
"Organizations deserve more attention than they have hitherto found-above all, a different sort of attention. This may seem a bold assertion given the many ways in which organizations are discussed in everyday communication and in the relevant scientific disciplines. But this is the very reason to concentrate our attention more strongly not on organizations as countable entities but on organization as a process. This is relevant from a theoretical perspective, given that inquiry into the essence of organization seems to have become unproductive (which is typical of questions of essence, indeed of what- questions per se). But a different understanding of organization could prove important for the purposes of practical policy. Precisely because organizations (again in the plural) have become crucial, indispensable to modern life, it could be important to have a better grasp of their "intrinsic logic." Especially if heteronomy-be it subjection to owners or other "masters," to liberal or socialist ideologies, or to representatives of interests that are themselves organized-is increasingly called into question, it could be important to give organizations a conception of themselves that enables them to answer for themselves"...